Model Hewan Uji Agen Terapeutik Alami pada Stroke Iskemik - Botutihe, Lisa Agustina; Safira, Rizka; Kintoko (Jurnal Ilmiah Farmasi, 2025)
Background: Ischemic stroke is an acute neurological injury resulting from focal damage to the central nervous system due to vascular obstruction and subsequent decrease in cerebral blood flow. Numerous animal models of ischemic stroke have been established to investigate its mechanism, pathophysiology, and risk factors. The animal model of ischemic stroke includes a global ischemia model and a focal ischemia model. This article describes various parameters, including hematological, biochemical, cytological, histological, and molecular factors, along with diverse biomarkers, that may support research in the development of novel, safer, and more effective therapeutic agents for ischemic stroke using animal models.Objective: This research seeks to determine the appropriate test animal model and parameters for ischemic stroke experiments.Method: A complete literature search was conducted across multiple databases, including NCBI, PubMed, and additional sources.Results: According to reference studies, the animal model test in the ischemic stroke experiment comprised a focal ischemia model and a global ischemic model. The focal ischemic model is more pertinent to ischemic stroke in humans compared to the global ischemic model. In addition, focal ischemic models, including Middle Cerebral Artery Occlusion (MCAO), have been utilized in over 40% of 2,582 nerve protection trials. The wide variety of test animal models possesses distinct advantages and disadvantages, making it crucial to select the appropriate model. The parameters of ischemic stroke, including hematology, biochemistry, cytology, histology, and molecular analysis, together with their biomarkers, can help in identifying the incidence of ischemic stroke in test animals.Conclusion: The focused ischemia model is a more pertinent animal model for ischemic stroke in relation to humans than the global ischemic model. Parameters utilized for the identification of ischemic stroke encompass hematology, biochemistry, cytology, histology, and molecular biology.